Pola asuh orang tua yang menikah di usia muda terhadap anak usia 0-6 tahun - Ahdar, Ahdar; Musyarif, Musyarif; Sahril, Sahril (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2023)
Children aged 0-6 years need parents who can help them develop themselves and overcome their problems well. The focus of this study is the development of children aged 0 to 6 years and guardians who marry young facing children aged 0 to 6 years. The aim of this research is to study how children aged 0 to 6 years develop and how the care of guardians who marry young in Kelapa Dua Village is handled. This research uses a type of logical exploration with emotional procedures. For guardians who marry young, perception and interview techniques are used to collect information, which is then investigated through deriving information, presenting information, and making conclusions. The results of the study show that there are three periods of development and improvement in adolescence, namely 0-6 years; The major problem is that children between 0 and 6 years old have limited jargon and have difficulty articulating different words accurately. From a practical point of view, there are two drawbacks, one of which is that children between the ages of 0 and 6 experience slight stunting in actual growth in terms of balance and healthy nutrition, as evidenced by imbalances in body weight and level. This is because children sometimes eat less and play more. Morality is the third defect, as children have moral questions. It is normal for children to be seen fighting with their parents. Soft parenting, dictatorial parenting, voice-based parenting and neglectful parenting are the four parenting styles used by young married parents to really target children aged 0 to 6 years.